Transcription factor BRCA1 is associated with BMPR1B transcriptional activity in sheep ovarian granulosa cells - Abdurahman, Anwar; Abulizi, Alimujiang; Abudukeremu, Abudukaibier; Zhang, Fei; Ga, Yuling; Obulkasim, Rahmantay (Frontiers in Veterinary Science, 2026)
BMPR1B is a well-characterized major gene associated with prolificacy in sheep. The FecB mutation in this gene promotes accelerated follicular development and increases ovulation rate, thereby enhancing litter size. Although BMPR1B plays a crucial role in reproduction, the regulatory mechanisms of its expression in sheep tissues are not yet fully understood. This study identified the promoter region of the BMPR1B gene and provided evidence that its transcriptional activity is associated with regulation by the transcription factor BRCA1. Luciferase reporter assays showed that the P1 fragment containing the BMPR1B promoter region had gene expression-driving activity; importantly, two BRCA1 binding sites (BBS) were identified within this promoter region. Subsequent experimental results suggest that BRCA1’s effect on BMPR1B transcriptional activity may be achieved through BBS2 rather than BBS1. Further studies in sheep ovarian granulosa cells (GCs) have shown that BRCA1 expression is correlated with BMPR1B expression and is linked to reduced granulosa cell apoptosis. Collectively, these findings provide a basis for the BRCA1-BMPR1B regulatory axis and offer new insights into the molecular framework influencing ovarian granulosa cell apoptosis in sheep.